Generic antiretroviral efficacy in AIDS-associated Kaposi's sarcoma in sub-Saharan Africa. - Mosam, Anisa; Cassol, Edana; Page, Taryn; Bodasing, Uvani; Cassol, Sharon; Dawood, Halima; Friedland, Gerald H; Scadden, David T; Aboobaker, Jamila; Jordaan, Jacobus P; Lalloo, Umesh G; Esterhuizen, Tonya M; et al. (AIDS (London, England), 2005)
Generic antiretroviral drugs are pivotal in the implementation of WHO's '3 by 5' programme. However, clinical experience with generics in sub-Saharan Africa is insufficiently documented. We report on 50 patients with HIV-associated Kaposi's sarcoma treated with generic fixed-dose highly active antiretroviral therapy. At 52 weeks, 74% achieved an undetectable viral load of < 50 copies/ml, 86% achieved < 400 copies/ml, and a 3.1 log10 decline from baseline. Side-effects were minimal. The outcomes support the use of generic antiretroviral therapy.
Keywords: Acquired Immunodeficiency Syndrome; Africa South of the Sahara; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Developing Countries; Drugs, Generic; Humans; Sarcoma, Kaposi; Treatment Outcome; Viral Load